2016
DOI: 10.1158/1078-0432.ccr-15-1915
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Mechanisms of Primary and Acquired Resistance to Third-Generation EGFR Inhibitors

Abstract: Purpose: To identify novel mechanisms of resistance to thirdgeneration EGFR inhibitors in patients with lung adenocarcinoma that progressed under therapy with either AZD9291 or rociletinib (CO-1686).Experimental Design: We analyzed tumor biopsies from seven patients obtained before, during, and/or after treatment with AZD9291 or rociletinib (CO-1686). Targeted sequencing and FISH analyses were performed, and the relevance of candidate genes was functionally assessed in in vitro models.Results: We found recurre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
194
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 227 publications
(211 citation statements)
references
References 43 publications
11
194
0
1
Order By: Relevance
“…Among the 43 patients, 11 (26%) had MET amplifications; of these, 7 patients presented only MET amplification, 3 had also SNV in other genes (PIK3CA and CDKN2A) and 1 presented concurrent HER2 amplification, similarly to Ortiz-Cuaran et al (13). The authors, analyzing an expanded cohort of 16 patients T790M-positive and with MET copy number gain in pre-treatment biopsies or plasma, observed that this group displayed significantly less tumor shrinkage and shorter median progression-free survival (PFS) than patients without MET alterations.…”
Section: Wz4002supporting
confidence: 59%
See 3 more Smart Citations
“…Among the 43 patients, 11 (26%) had MET amplifications; of these, 7 patients presented only MET amplification, 3 had also SNV in other genes (PIK3CA and CDKN2A) and 1 presented concurrent HER2 amplification, similarly to Ortiz-Cuaran et al (13). The authors, analyzing an expanded cohort of 16 patients T790M-positive and with MET copy number gain in pre-treatment biopsies or plasma, observed that this group displayed significantly less tumor shrinkage and shorter median progression-free survival (PFS) than patients without MET alterations.…”
Section: Wz4002supporting
confidence: 59%
“…Also Ortiz-Cuaran et al showed high-level amplification of MET either in tumor biopsy collected before treatment in a patient that experienced primary resistance to rociletinib and in the post-treatment biopsy of a patient that developed resistance after stable disease to osimertinib (13). Thanks to in vitro models they could provide functional evidence that HER2 and MET amplification may induce innate and acquired resistance to this new class of EGFR inhibitors, confirming clinical observations (13).…”
Section: Wz4002mentioning
confidence: 69%
See 2 more Smart Citations
“…Preclinical studies have also identified potential resistance mechanisms. For example, cells that are resistant to osimertinib appear to have enhanced levels of phosphorylated MEK and may be particularly sensitive to combined EGFR and MEK inhibition [57,58]. The identification of heterogeneous resistance mechanisms to osimertinib has prompted the initiation of several early-phase clinical trials [59].…”
Section: Factors Influencing First-line Treatment Choice: Mechanisms mentioning
confidence: 99%